Answer:
(13, -10, -7)
Explanation:
Given
x+y+z=−4 .................. 1
2x+3y−2z=10 .................... 2
−x+2y−3z=−12 ................... 3
Reduce the equation to two equations, two unknowns:
Add eqn 1 and 3
y+2y+(z-3z) = -4-12
3y - 2z = -16 .......... 4
Also multiply eqn 3 by 2:
−2x+4y−6z=−24 ................... 5
Add 2 to 5:
3y+4y+ (-2z-6z) = 10-24
7y-8z = -14 ............... 6
Equate 4 and 6
3y - 2z = -16 .......... 4 * 4
7y-8z = -14 ............... 6 * 1
...............................................
12y - 8z = -64
7y-8z = -14
Subtract the resulting equations
12y-7y = -64+14
5y = -50
y = -50/5
y = -10
Substitute y = -10 into equation 4 to get z:
3y - 2z = -16
3(-10)-2z = -16
-30-2z = -16
-2z = -16+30
-2z = 14
z = 14/-2
z = -7
Substitute y = -10, z = -7 into eqn 1 to get x:
x+y+z = -4
x-10-7 = -4
x-17 = -4
x = -4+17
x = 13
Hence (x, y, z) is (13, -10, -7)